2012
DOI: 10.1002/anie.201108849
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Design of Highly Active and Selective Catalysts for Phosgene‐Free Synthesis of Aromatic Polyurethanes

Abstract: Catalyst design: First principles calculations predict that phosgene can be substituted by dimethyl carbonate (DMC) in the carbamoylation of aromatic amines when using a CeO2 catalyst preferentially exposing the low energy {111} facet. Experimental results confirm the theoretical predictions, and CeO2 nano‐octahedra terminated by low energy {111} facets show high activity and selectivity toward the desired dicarbamoylated product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 8 publications
3
35
0
Order By: Relevance
“…15 However, due to the high reactivity of the intermediates decomposed from DMC, carbamoylation and methylation proceed simultaneity during the aminolysis reaction, which, respectively, leads to the formation of MPC and N-methylaniline (NMA) and/or N,N 0 -dimethylaniline (DMA), as shown in Scheme 1. 2,[16][17][18] Thus, developing catalysts with high activity is quiet necessary so as to enhance the selectivity as well as yield of MPC.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, due to the high reactivity of the intermediates decomposed from DMC, carbamoylation and methylation proceed simultaneity during the aminolysis reaction, which, respectively, leads to the formation of MPC and N-methylaniline (NMA) and/or N,N 0 -dimethylaniline (DMA), as shown in Scheme 1. 2,[16][17][18] Thus, developing catalysts with high activity is quiet necessary so as to enhance the selectivity as well as yield of MPC.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative carbonylation of primary aromatic amines to generate the corresponding carbamates is well known , and is also the key step from TDA to TDC in the alternative (CO 2 ‐based) route towards TDI as high‐value polymer precursor (Scheme ). Apart from this, the synthesis of TDC via reductive carbonylation of nitro compounds and reactions of amines with organic carbonates , CO 2 or corresponding ureas with alcohols are competing concepts – but do not address our needs in such a completive way.…”
Section: Oxidative Carbonylationmentioning
confidence: 99%
“…Zhou et al [113] first reported that CeO 2 nanorods, exposing preferentially {0 0 1} and {1 1 0} facets, showed a substantially higher surface-specific activity for CO oxidation than CeO 2 nanocrystals of irregular shapes, for which the majority of the surface facets corresponded to more compact {1 1 1} planes. More recently, Laursen et al found CeO 2 octahedra nanocrystals terminated by {1 1 1} facets to exhibit the highest activity and selectivity toward the desired dicarbamoylated products in the carbamoylation of aromatic amines with dimethyl carbonate, a reaction which is crucial in potential ''greener,'' phosgene-free processes to produce polyurethanes [114]. Given that many oxides play a non-innocent role when applied as support material in metal catalysts, similar facetdependent catalytic properties have been revealed for metal nanoparticles deposited on morphologically tailored oxide supports.…”
Section: Recent Examples For the Use Of 3d Model Systems To Guide Catmentioning
confidence: 99%